2008
DOI: 10.1002/path.2394
|View full text |Cite
|
Sign up to set email alerts
|

Phagocyte‐specific S100 proteins are released from affected mucosa and promote immune responses during inflammatory bowel disease

Abstract: Phagocyte-derived S100 proteins are endogenous activators of innate immune responses. S100A12 binds to the receptor for advanced glycation end-products, while complexes of S100A8/S100A9 (myeloid-related proteins, MRP8/14; calprotectin) are ligands of toll-like receptor 4. These S100 proteins can be detected in stool. In the present study we analyse the release of S100A12 and MRP8/14 from intestinal tissue. Specimens from patients with Crohn's disease (CD; n = 30), ulcerative colitis (UC; n = 30), irritable bow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
134
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(146 citation statements)
references
References 45 publications
8
134
0
4
Order By: Relevance
“…In line with these functions, phagocytes reportedly express S100A8 and S100A9 under multiple inflammatory conditions, i.e., inflammatory bowel disease, rheumatoid arthritis or allograft rejection (8)(9)(10), whereas numerous pathological conditions associated with inflammation in humans are associated with elevated S100A8 and S100A9 levels (11). Furthermore, the inflammatory factors interleukin (IL)-1, interferon (IFN)-γ and tumor necrosis factor (TNF)-α induce the expression and secretion of the S100A8/A9 heterodimer (12)(13)(14).…”
mentioning
confidence: 94%
“…In line with these functions, phagocytes reportedly express S100A8 and S100A9 under multiple inflammatory conditions, i.e., inflammatory bowel disease, rheumatoid arthritis or allograft rejection (8)(9)(10), whereas numerous pathological conditions associated with inflammation in humans are associated with elevated S100A8 and S100A9 levels (11). Furthermore, the inflammatory factors interleukin (IL)-1, interferon (IFN)-γ and tumor necrosis factor (TNF)-α induce the expression and secretion of the S100A8/A9 heterodimer (12)(13)(14).…”
mentioning
confidence: 94%
“…Although the role of this protein in zebrafish is still unknown, S100 proteins are endogenous activators of innate immune responses in mammals, and some of them have proinflammatory properties and are associated with different inflammatory diseases, such as inflammatory bowel disease. [82][83][84] Several genes involved in the relief of oxidative stress as a compensatory mechanism were up-modulated in tolerized zebrafish as described for mammals 85,86 ; these include glutathione peroxidase 7 (GPX7), which mitigates the organ dysfunction during chronic inflammation, and phosphoenolpyruvate synthase, which is an essential enzyme when pyruvate and lactate are used as a carbon source. The upmodulation in tolerized fish suggests a mechanism for avoiding the excess of lactate and hypoxia that induces the organ failure associated with sepsis.…”
Section: Transcriptome In Lps Tolerancementioning
confidence: 99%
“…Furthermore, the study revealed that S100 alarmins were produced by vaginal epithelial cells following interaction with C. albicans. S100 alarmins are cytosolic and secretory proteins produced by a variety of cell types, including PMNs, monocytes, and epithelial cells (14)(15)(16)(17)(18). In VVC, epithelial cell-derived S100 alarmins are suggested to be secreted in response to C. albicans as an initial signal for PMN migration, which becomes amplified further by subsequent production via recruited PMNs in the vaginal cavity.…”
mentioning
confidence: 99%